Magnetic resonance imaging in the evaluation of patients with aseptic meningoencephalitis and connective tissue disorders - APPENZELLER,SIMONE (2000)
OBJECTIVE: To describe the role of magnetic resonance imaging (MRI) in the evaluation of patients with chronic and recurrent aseptic meningitis.METHOD: A retrospective study of five patients with aseptic meningoencefalitis diagnosed by clinical and CSF findings. CT scans showed without no relevant findings. RESULTS: MRI showed small multifocal lesions hyperintense on T2 weighted images and FLAIR, with mild or no gadolinium enhancement, mainly in periventricular and subcortical regions. Meningoencephalitis preceded the diagnosis of the underlying disease in four patients (Behçet´s disease or systemic lupus erythematosus). After the introduction of adequate treatment for the rheumatic disease, they did not present further symptoms of aseptic meningoencephalitis. CONCLUSION: Aseptic meningoencephalitis can be an early presentation of an autoimmune disease. It is important to emphasize the role of MRI in the diagnosis and follow-up of these patients.